2019
DOI: 10.1016/j.eneco.2019.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Volatility forecasting in commodity markets using macro uncertainty

Abstract: In this paper, we empirically examine the predictive power of macroeconomic uncertainty on the volatility of agricultural, energy and metals commodity markets. We find that the latent macroeconomic uncertainty measure of Jurado et al. (2015) is a common volatility forecasting factor for commodity markets, which provides statistically significant volatility predictions for forecasting horizons up to twelve months ahead. The results indicate that the forecasting power of macroeconomic uncertainty is higher when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(14 citation statements)
references
References 67 publications
(111 reference statements)
0
14
0
Order By: Relevance
“…Besides these commodity‐specific factors, commodity markets are also well known to be affected by macroeconomic factors. Bakas and Triantafyllou (2019) find that the latent macroeconomic uncertainty measure is a common volatility forecasting factor for commodity markets. However, there is still debate about the predictability of risk factors since previous studies have shown mixed results, examples include Daskalaki et al (2014), Fernandez‐Perez et al (2018), and others.…”
Section: Introductionmentioning
confidence: 99%
“…Besides these commodity‐specific factors, commodity markets are also well known to be affected by macroeconomic factors. Bakas and Triantafyllou (2019) find that the latent macroeconomic uncertainty measure is a common volatility forecasting factor for commodity markets. However, there is still debate about the predictability of risk factors since previous studies have shown mixed results, examples include Daskalaki et al (2014), Fernandez‐Perez et al (2018), and others.…”
Section: Introductionmentioning
confidence: 99%
“…However, these models are based on time‐series data, ignoring the significance of external influencing factors, such as extreme weather, emergencies, and sentiment in agricultural markets. Moreover, the measurement of these factors is still an open question (Adämmer & Bohl, 2018; Ahumada & Cornejo, 2016a; Bakas & Triantafyllou, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ma et al (2018) find that the EPU index has significant predictive power for oil volatility out-of-sample. Bakas and Triantafyllou (2019) indicate that macro uncertainty generates significant predictive power for oil volatility, and Mei et al (2020) and Liu et al (2021) reveal that geopolitical risk improves oil volatility prediction. Therefore, the estimated conditional variance derived from uncertainty information will have smaller biases from the true but unobservable volatility of oil prices.…”
Section: Introductionmentioning
confidence: 99%